T-type calcium channel as a portal of iron uptake into cardiomyocytes of beta-thalassemic mice - Kumfu S. (2014)
Objectives: Iron-overload condition can be found in β-thalassemic patients with regular blood transfusion, leading to iron deposition in various organs including the heart. Elevated cardiac iron causes iron-overload cardiomyopathy, a condition that provokes mortality because of heart failure in patients with thalassemia. Previous studies demonstrated that myocardial iron uptake may occur via L-type calcium channels (LTCCs). However, direct evidence regarding the claimed pathway in thalassemic cardiomyocytes has never been investigated. Methods: Hearts from genetic-altered β-thalassemic mice and adult wild-type mice were used for cultured ventricular cardiomyocytes. Blockers for LTCC, T-type calcium channel (TTCC), transferrin receptor1 (TfR1), and divalent metal transporter1 (DMT1) were used, and quantification of cellular iron uptake under various iron loading conditions was performed by Calcein-AM fluorescence assay. Microarray analysis was performed to investigate gene expressions in the hearts of these mice. Results: This study demonstrated that iron uptake under iron-overload conditions in the cultured ventricular myocytes of thalassemic mice was greater than that of wild-type cells (P < 0.01). TTCC blocker, efonidipine, and an iron chelator, deferoxamine, could prevent iron uptake into cultured cardiomyocytes, whereas blockers of TfR1, DMT1, and LTCC could not. Microarray analysis from thalassemic hearts demonstrated highly up-regulated genes of TTCC, zinc transporter, and transferrin receptor2. Conclusions: Our findings indicated that iron uptake mechanisms in cultured thalassemic cardiomyocytes are mainly mediated by TTCC, suggesting that TTCC is the important pathway for iron uptake in this cultured thalassemic cardiomyocyte model. © 2010 John Wiley & Sons A/S.